Effect of Vitronectin Bound to Insulin-Like Growth Factor-I and Insulin-Like Growth Factor Binding Protein-3 on Porcine Enamel Organ-Derived Epithelial Cells - Yoshinori Shinohara; Shuhei Tsuchiya; Kazuo Hatae; Masaki J. Honda (International Journal of Dentistry)
The aim of this paper was to determine whether the interaction between IGF, IGFBP, and VN modulates the functions of porcine EOE cells. Enamel organs from 6-month-old porcine third molars were dissociated into single epithelial cells and subcultured on culture dishes pretreated with VN, IGF-I, and IGFBP-3 (IGF-IGFBP-VN complex). The subcultured EOE cells retained their capacity for ameloblast-related gene expression, as shown by semiquantitative reverse transcription-polymerase chain reaction. Amelogenin expression was detected in the subcultured EOE cells by immunostaining. The subcultured EOE cells were then seeded onto collagen sponge scaffolds in combination with fresh dental mesenchymal cells and transplanted into athymic rats. After 4 weeks, enamel-dentin-like complex structures were present in the implanted constructs. These results show that EOE cells cultured on IGF-IGFBP-VN complex differentiated into ameloblasts-like cells that were able to secrete amelogenin proteins and form enamel-like tissues in vivo. Functional assays demonstrated that the IGF/IGFBP/VN complex significantly enhanced porcine EOE cell proliferation and tissue forming capacity for enamel. This is the first study to demonstrate a functional role of the IGF-IGFBP-VN complex in EOE cells. This application of the subculturing technique provides a foundation for further tooth-tissue engineering and for improving our understanding of ameloblast biology.